Dolichosin A, a coumestan isolated from Glycine tabacina, inhibits IL-1β-induced inflammation in SW982 human synovial cells and suppresses RANKL-induced osteoclastogenesis: From network pharmacology to experimental pharmacology. (10th August 2020) - Tu, Yanbei; Wang, Kai; Tan, Lihua; Han, Bing; Hu, Yuanjia; Ding, Hang; He, Chengwei
Abstract: Ethnopharmacological relevance: Glycine tabacina (Labill.) Benth has been used as a traditional Chinese herbal medicine for the treatment of rheumatoid arthritis (RA) and joint infection. It is also one of the sources of the renowned native herbal medicine 'I-Tiao-Gung' in Taiwan. Aim of the study: This study aimed to investigate anti-arthritic effects and underlying mechanisms of dolichosin A (DoA), a coumestan compound isolated from G. tabacina, by the integration of network pharmacology and experimental pharmacology. Materials and methods: Putative therapeutic targets and potential pharmacological mechanisms of DoA for RA treatment were predicted by network pharmacology approach. The regulated network of DoA acting on RA was constructed using Cytoscape 3.7.1. Anti-arthritic effects of DoA and predicted mechanisms were further validated using IL-1β-induced SW982 human synovial cell model and RANKL-induced osteoclastogenesis model. Results: A regulatory network of DoA-targets-pathways-RA was successfully constructed using network pharmacology approach. In this network, 65 candidate targets of DoA related to its therapeutic effect on RA were identified and the functional enrichment analysis revealed that these candidate targets were significantly involved in 12 central signaling pathways such as PI3K/AKT pathway, MAPK pathway and osteoclast differentiation. Furthermore, we found that DoA could significantly inhibit IL-1β-induced inflammation in SW982 human synovial cells, as evidenced by the decreased levels of pro-inflammatory mediators (TNF-α, IL-6 and COX-2) and MMP-3. DoA also suppressed RANKL-induced osteoclastogenesis in vitro, as evidenced by decreased number of TRAP-positive multinucleated osteoclasts and reduced TRAP activity. Further experimental mechanism evidence confirmed the predicted results of network pharmacology that the blockade of PI3K/AKT and MAPK pathways activation was closely associated with these regulated processes of DoA. Conclusions: Our results demonstrated that DoA exhibited strong anti-arthritic activity through suppressing PI3K/AKT and MAPK pathways activation in activated synovial cells and osteoclasts, suggesting its potential as a hopeful candidate for the development of novel agents for the prevention and treatment of RA. Graphical abstract: Image 1